Simulation and Analysis of HEMP Coupling Effect on a Wire Inside an Apertured Cylindrical Shielding Cavity - Song, Shu-Ting; Jiang, Hong; Huang, Yu-Lan (Applied Computational Electromagnetics Society Journal (ACES), 2022)
High altitude nuclear electromagnetic pulse (HEMP) can damage electronic equipments of radar and communication systems. Back door coupling is one of the main ways of HEMP attacks on the electronic devices. In this paper, the three-dimensional (3D) electromagnetic (EM) simulation software MicroStripes7.5, which is based on the transmission line matrix (TLM) method, are employed to investigate the HEMP coupling effect on a wire located inside a cylindrical shielding cavity having one or few apertures. The EM models of the wire and the apertured shielding cavity are constructed, and the induced wire currents through the aperture of cavity are simulated. By comparing the simulation results of the wire with and without shield of the cavity, the shielding effectiveness (SE) is calculated. Further, the effects on induced wire in various cases are compared and analyzed, including single-aperture and multiple-aperture, different incident angles, polarization angles, and wire locations. Also, the cylindrical cavity is compared with the rectangular cavity.